2015
DOI: 10.1002/lary.25500
|View full text |Cite
|
Sign up to set email alerts
|

Approach to en bloc resection and reconstruction of primary masticator space malignancies

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, new surgical techniques, such as endoscopicassisted access to the masticator space, and improved reconstruction techniques have allowed for growing evidence that some of these lesions may in fact be amenable to surgical extirpation, with a reasonable possibility of achieving negative margins and improved functional outcomes. [3][4][5][6][7]10,14 In this study, we examined all cases of T4b OCSCC in the NCDB and investigated the outcome of different treatment approaches. We found that patients who were treated with primary surgery 1 CRT experienced longer survival as compared with those treated with CRT alone on multivariable and propensity score-matched analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, new surgical techniques, such as endoscopicassisted access to the masticator space, and improved reconstruction techniques have allowed for growing evidence that some of these lesions may in fact be amenable to surgical extirpation, with a reasonable possibility of achieving negative margins and improved functional outcomes. [3][4][5][6][7]10,14 In this study, we examined all cases of T4b OCSCC in the NCDB and investigated the outcome of different treatment approaches. We found that patients who were treated with primary surgery 1 CRT experienced longer survival as compared with those treated with CRT alone on multivariable and propensity score-matched analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Up‐front surgery might not be considered for T4b tumors of the oral cavity due to the difficulty in obtaining adequate margins. However, new surgical techniques, such as endoscopic‐assisted access to the masticator space, and improved reconstruction techniques have allowed for growing evidence that some of these lesions may in fact be amenable to surgical extirpation, with a reasonable possibility of achieving negative margins and improved functional outcomes 3–7,10,14 . In this study, we examined all cases of T4b OCSCC in the NCDB and investigated the outcome of different treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third division of the trigeminal nerve and its branches passes through this space, and the internal maxillary artery with its branches runs through this space and enters the pterygopalatine fossa13. Several spaces are in contact with the masticator space, such as the buccal and retroantral spaces anteriorly, parapharyngeal space medially, and parotid space laterally.…”
Section: Discussionmentioning
confidence: 99%
“…The Conley's lateral approach of extending the preauricular incision to the neck with a second submandibular incision has been proposed but has the disadvantages of facial incision and bony defect along with the sacrifice of inner deep structures14. Later, Castro et al13 revised this method and published an approach to malignant tumors of the masticator space through a preauricular incision and transcervical incision; however, this method also has the burden of bypassing facial nerve trunks to access inner neoplasms. Dingman and Conley15 introduced an inferior approach through the submandibular incision that included midline lip splitting and posterior extension to the mastoid process.…”
Section: Discussionmentioning
confidence: 99%